If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 9(x + 2) * 2 + -15 Reorder the terms: 0 = 9(2 + x) * 2 + -15 Reorder the terms for easier multiplication: 0 = 9 * 2(2 + x) + -15 Multiply 9 * 2 0 = 18(2 + x) + -15 0 = (2 * 18 + x * 18) + -15 0 = (36 + 18x) + -15 Reorder the terms: 0 = 36 + -15 + 18x Combine like terms: 36 + -15 = 21 0 = 21 + 18x Solving 0 = 21 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. 0 + -18x = 21 + 18x + -18x Remove the zero: -18x = 21 + 18x + -18x Combine like terms: 18x + -18x = 0 -18x = 21 + 0 -18x = 21 Divide each side by '-18'. x = -1.166666667 Simplifying x = -1.166666667
| y^2-22y-3=0 | | y=-8/5-12/5 | | 5abc*b+45= | | 7x+3(x-2)+6=x+36 | | -3/4(12x-8)-18 | | -4+4p=12 | | -4r^4+5r^2+6=0 | | 10x-5=2r+10 | | x+43=18 | | -4r^2+5r^2+6=0 | | 13.682=63.54-9.7 | | m,7+4=-8 | | 5x-4=x-2 | | 34x-5y=8 | | 7=y/6 | | x-2=5x-4x | | 2[x-6]+14=-38 | | 2(p-5)=12 | | 105x=x+112 | | 5x+4=x-28 | | 3x-13=10+11 | | 4x-8=10x+3 | | 5X+3=8x+24 | | r(x)=8/3x-16 | | 13-3/3=37 | | 6-4v=-22 | | 3x-8=1x+4 | | -75=-5(u+8) | | 3timesd=45 | | 6(4x+7)2=282 | | 8v+6=-42 | | 3xd=45 |